Use of 3D printers for the development of active methodologies in Engineering courses (Research, Society and Development, 2021)
I this research aimed to verify the importance of the use of Additive Manufacturing in engineering teaching with the use of Active Methodologies. The study presents the results of the students' experience with the use of 3D Printers in Active Methodologies activities. Their experiences and perceptions showed the implications of applying these practices in the classroom. A case study was conducted to better understand the phenomenon studied. A literature literature review was also conducted to get a global view of the field of research. A selective reading was required, the contents were analyzed and an online form was applied in interview format for data collection. It was possible to verify how the use of Active Methodologies and Additive Manufacturing connects and enables the projects developed by the students ensuring interactive and dynamic classes, where the development of critical and analytical thinking is stimulated for decision making. This research can be used as a guide for teachers and engineers to realize the real importance of PBL practices with the use of 3D printers, presented in this study.